Investigating the effect of gas flow on the drag reduction performance in multiphase flow system - Noor Ashikin, Ohyanuddin (2012)
The study on drag reduction towards multiphase flow system which in the fluid flow systems become interest towards the academic and industrial during the past several decades as it can give benefit to many industrial applications such as oil well operations, fire fighting, heating and cooling water circuits and biomedical system when drag reduction is reduce. The flow transitions inside the pipeline itself can give the effect to the drag reduction performance. It can offer large economic advantages and larger effectiveness in the transportation of the fluid. The objectives of the research are to investigate the effect of gas flow rate on drag reduction performance and to investigate the drag reduction ability from the effect of gas flow rate in the multiphase flow system. The research is carried out by sieving the sand to get different sand. Then, the main reservoir is filled with ≈ 450 kg water and the sand is mixed together. The solution is passed through 1.5 inch pipe and compressed air is supplied to the solution at a point of pipeline The turbulent drag reductions are measured by reading the value of pressure drop along the re-circulatory flow. Experimental works are repeated with the other liquid velocity, sand concentration, sizes and without presence of air. From the research, the results show that occurrence of gas flow will increase the drag reduction in all conditions. Drag reduction ability increase when effect of gas flow occurs in multiphase flow system. Drag reduction is believed can be strongly influenced by the concentration of particles The influence of drag reduction on the turbulence worked better at higher Reynolds number. The percentage of drag reduction is also affected by the concentration and size of the particle, where it is more favored towards higher concentration and larger particle sizes.